Crowd Simulation - Thalmann, Daniel; Musse, Soraia Raupp; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2007)
Research into the methods and techniques used in simulating crowds is now reaching maturity, but until now there is no book that focuses on this important topic. Prior approaches have been application-specific focusing on different aspects of collective behaviour and using different modelling techniques. Thalmann and Musse have identified two broader areas of crowd simulations, firstly focusing on the realism of behavioural aspects and secondly looking at how to achieve high quality visualisation. The study of crowds is complex with issues such as collision avoidance problems relating to large numbers of individuals; motion planning, trajectories and so forth. Depending on the application of crowds, other requirements such as real-time simulations are needed to populate virtual environments in VR systems. In order to provide a tool to simulate behavioural aspects of a crowd, social conventions of inter-relationships are needed. Crowd requirements and potential strategies are discussed in this book and topics covered include population modelling, virtual human animation and computer vision techniques that are focused on crowd control and crowd rendering.
State-of-the-Art -- Modeling of Populations -- Virtual Human Animation -- Behavioral Animation of Crowds -- Relating Real Crowds with Virtual Crowds -- Crowd Rendering -- Populated Environments -- Applications: Case Studies -- Book Contribution.
Keywords: Optical data processing; Computer graphics; Computer simulation; Pattern recognition; Image Processing and Computer Vision; Computer Graphics; Simulation and Modeling; Pattern Recognition